2012
DOI: 10.1177/0018720812460246
|View full text |Cite
|
Sign up to set email alerts
|

Control Task Substitution in Semiautomated Driving

Abstract: Objective: The study was designed to show how driver attention to the road scene and engagement of a choice of secondary tasks are affected by the level of automation provided to assist or take over the basic task of vehicle control. It was also designed to investigate the difference between support in longitudinal control and support in lateral control. Background:There is comparatively little literature on the implications of automation for drivers'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(91 citation statements)
references
References 19 publications
7
83
0
1
Order By: Relevance
“…For example, it has been experimentally found that people are inclined to watch DVDs in a highly automated car (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013). Furthermore, over 30 driving simulator studies have measured a reduction of self-reported workload in sophisticated driving simulator studies, (see De Winter, Happee, Martens, & Stanton, 2014, for a review), which matches the results of our questions regarding task difficulty (Q25-27).…”
Section: Discussionsupporting
confidence: 59%
“…For example, it has been experimentally found that people are inclined to watch DVDs in a highly automated car (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013). Furthermore, over 30 driving simulator studies have measured a reduction of self-reported workload in sophisticated driving simulator studies, (see De Winter, Happee, Martens, & Stanton, 2014, for a review), which matches the results of our questions regarding task difficulty (Q25-27).…”
Section: Discussionsupporting
confidence: 59%
“…Beyond that, it is also possible that the system might require a transfer to Level 2 if the conditions necessitate it (Creaser & Fitch, 2015). An automated driving system will allow the driver to take his eyes off the road and engage in NDRTs and driving simulator studies show that drivers are willing to do so, possibly increasing the demand of a take-over situation (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013;Radlmayr, Gold, Lorenz, Farid, & Bengler, 2014). This act of reliance is only performed if the driver trusts driving automation enough to completely hand over the driving task.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 99%
“…use of in-vehicle entertainment. Carsten and colleagues (Carsten, Lai, Barnard, Jamson, & Merat, 2012) found that engagement in non-driving tasks, like reading or usage of a DVD player, increased from manual to highly automated driving as a substitution for the vehicle control task. Llaneras, Salinger and Green (2013) reported similar results with engagements like eating or e-mailing.…”
Section: Engagement In a Non-driving Task As Use Case In Highly Autommentioning
confidence: 99%